2023
DOI: 10.1177/20563051221150407
|View full text |Cite
|
Sign up to set email alerts
|

Developing Misinformation Immunity: How to Reason-Check Fallacious News in a Human–Computer Interaction Environment

Abstract: To counter the fake news phenomenon, the scholarly community has attempted to debunk and prebunk disinformation. However, misinformation still constitutes a major challenge due to the variety of misleading techniques and their continuous updates which call for the exercise of critical thinking to build resilience. In this study we present two open access chatbots, the Fake News Immunity Chatbot and the Vaccinating News Chatbot, which combine Fallacy Theory and Human–Computer Interaction to inoculate citizens a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…Fallacy theory derives from logic theory and relates to arguments that seem correct but are not (Musi & Reed, 2022), thereby misleading. Musi et al (2023) adopted the Fallacy theory to counter the fake news phenomenon using immunity chatbots. Likewise, Musi & Reed (2022), through the lens of this theory, address misinformation issues by providing a systematic approach for classifying and analyzing different types.…”
Section: Resultsmentioning
confidence: 99%
“…Fallacy theory derives from logic theory and relates to arguments that seem correct but are not (Musi & Reed, 2022), thereby misleading. Musi et al (2023) adopted the Fallacy theory to counter the fake news phenomenon using immunity chatbots. Likewise, Musi & Reed (2022), through the lens of this theory, address misinformation issues by providing a systematic approach for classifying and analyzing different types.…”
Section: Resultsmentioning
confidence: 99%
“…Some studies indicate a positive influence, while others suggest limitations or context-dependent effects. It can be said that particularly in educational, professional, and informational contexts (8,22). Critical thinking, a crucial skill involving the objective analysis and evaluation of an issue to form a judgment, can be significantly impacted by the use of chatbots.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, one concluded that ChatGPT can potentially enhance academic processes, which may include aspects of critical thinking (5). Musi (2023) presents chatbots designed to inoculate against misinformation, which could indirectly enhance critical thinking skills (22). Haspari & Wu (2022) believe how AI chatbots can foster critical thinking in the context of language learning (23).…”
Section: Critical Thinkingmentioning
confidence: 99%
“…In England and Norway, while digital technologies are recognised as important tools, they are not given the same level of emphasis. Familiarity with navigating digital technologies is important given the rapid changes in societal requirements; it is essential for students to cultivate their thinking and reasoning skills to effectively handle instances of misinformation and meet the demands of the future workforce (Goodsett, 2020; Musi et al., 2023).…”
Section: Introductionmentioning
confidence: 99%